Towards a decent labour market for low waged migrant workers - Rijken, Conny; Lange, Tesseltje de (Amsterdam University Press, 2018)
This anthology analyzes low-wage migrant workers in Europe from many perspectives, including migration policies, human rights, economics, and more. Free movement of workers and services in the EU calls into question the extent to which the labor market and its institutions are able to counteract negative consequences, such as downward wage pressures and abuse of workers. These essays flesh out the imbalances that unfairly disadvantage low-wage workers, shed light on their causes, and discuss possible solutions.